Pengembangan wisata pantai melalui peran serta kelompok IRT Nelayan Di Desa Teluk Rhu Rupat Utara - Feliatra Feliatra; Ummi Mardhiah Batubara; Iesje Lukistyowati; Mardalisa Mardalisa; Lamun Batara (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
One of the potentials in Teluk Rhu Village is beach tourism. The development of coastal tourism in Teluk Rhu Village needed a principal role from the Women's Fishermen, specifically to make processed products from fishermen's catch. The community service activity aims to improve the Women Fishermen's knowledge and skills in making processed fishery products that can be marketed at coastal tourist locations. This program implementation used the PALS (Participatory Action and Learning System) method with three stages. There was socialization, increasing knowledge, and direct practice. The community service activities showed that there was potential to develop coastal tourism in Teluk Rhu Village. The several potentials were the Women Fishermen can get the raw material easily, they have a lot of time used to produce and sell the products, and they have skills to make some processed food with diversification techniques such as nugget, meatball, and otak-otak. Thus, Increasing the knowledge and skills of the Women's fishermen through diversification technology can be used to increase the number of tourists at the coastal tourist location of Teluk Rhu Village, Rupat Utara District.